A REVIEW ON THE PSYCHOLOGICAL ISSUES AND PSYCHOSOCIAL INTERVENTION: FLOOD DISASTERS IN MALAYSIA - Akhir, Noremy Md. (International Journal of Psychosocial Rehabilitation, 2020)
In Malaysia, flood disasters are distinguished from other types of collective stress because flood disaster is a crisis. Regardless of the level of injury or loss experience, most of the victims in the affected area will face a certain amount of emotional distress and anxiety. It is because during, flood disasters, individuals, families and communities suffer from trauma and stress in every dimension of their lives especially from the loss of life and health, properties, personal belonging, job, community infrastructure and social ties. The physical impact of flooding contributes to psychological, emotional and social effect in these victims. As a result, they exhibit reactionary patterns in terms of emotions, mental and behaviour which, will be elaborated in this article. Considering the psychological issues as a result of the flood disaster in Malaysia, it is necessary to provide psychosocial intervention. Therefore, psychosocial care and support is an essential component. Thus, intervention and psychosocial rehabilitation are also discussed in this article. The key element of psychosocial intervention is the concept of resilience and the involvement of community members in providing psychosocial support to overcome the psychological issues faced by flood victims.